The Influence of Technological Peculiarities on Fermented Sausages’ Quality and Sensory Properties - Gramatina Ilze (Sciendo, 2021)
Fermentation is one of the ancient technological processes used in food production which influences the shelf-life of meat and meat products, also significantly affects the sensory properties like aroma and flavour. The objective of the present study was to evaluate the elaborated technology for a new fermented sausage production on the product quality and sensory properties. Sausages were produced by the standard technology using glucono-delta-lactone or starter culture. The drying of samples differs from 3 to 4 weeks at the same conditions; samples were dried for 4 weeks which produced with the starter culture, and 3 weeks which produced with glucono-delta-lactone. The sausages were tested at the end of the production, analysing pH, water activity, moisture and salt content, as well as the presence of Listeria monocytogenes, colony forming units of Listeria monocytogenes and Enterobacteriaceae in the sausage samples were analysed. The sensory evaluation was organised after getting Listeria monocytogenes testing results.